Memorandum on the Appraisal and Prospects of the Second Five Year Plan - Planning Commission, Government of India (Planning Commission, Government of India, 1956)
During 1957-58, the shortage of foreign exchange resources presented a pressing problem. The salient features of this problem are presented in the Economic Survey for 1958-59 and in the paper on the Fall of Foreign Exchange Reserves which was placed before Parliament. As explained in these papers, it became necessary not only to distinguish certain projects which called for substantial amounts of foreign exchange as the “core”, but also to consider the possibility of adjusting allocations for different sectors and to examine afresh the size of the Plan. With the drawing up of the Development Plan for 1958-59, it has become possible for the Planning Commission to review the achievements of the first two years and the targets for the third year, and also to estimate the likely trends and requirements for the last two years of the Plan.
Planning Commission Government of India
Planning Commission, Government of India
Keywords: Second Five Year Plan- India; Economic development and planning in India